Predicting the dynamic environment.
The paper discussed the essential part of company strategy which is to plan for adapting company action to its environment. New technology social shifts, political realignments and pressures, as well as the more common recognized economic changes were included in the discussion.
Change -- Dynamic setting of business: technological changes; Social and political changes; Economic changes; Stress and strain; Selecting critical features of the environment; Forecasting techniques; Economic forecasting; technological forecasting; Making use of forecasts -- Summary.
Mimeographed.
Keywords: Technological innovations -- Environmental aspects; Social change; Environmental policy